2004
DOI: 10.1161/01.res.0000143013.04985.e7
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Resident Cells Play a Dominant Role in Arteriogenesis and Concomitant Macrophage Accumulation

Abstract: Abstract-Collateral growth is characterized by macrophage accumulation, suggesting an important role of circulating cells. To study origin and function of macrophages during arteriogenesis, we related the extent of macrophage accumulation to vascular proliferation and investigated the fate of fluorescently (CMFDA) labeled blood cells that were injected at the time of femoral artery occlusion. The effect of bone marrow depletion via cyclophosphamide before femoral artery occlusion on collateral proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 35 publications
(46 reference statements)
6
84
0
1
Order By: Relevance
“…These findings are also quite different to the previous understanding that proliferation of resident cells induces venogenesis. 3,4) In the present study, β-MNCs migrated into the coronary vessel wall, not from the lumen but from outside, ie, the interstitial space, and contributed to arteriogenesis and venogenesis. This finding is also different to the previous understanding that circulating stem cells/precursor cells migrate into the vessel wall from the lumen and contribute to angiogenesis.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These findings are also quite different to the previous understanding that proliferation of resident cells induces venogenesis. 3,4) In the present study, β-MNCs migrated into the coronary vessel wall, not from the lumen but from outside, ie, the interstitial space, and contributed to arteriogenesis and venogenesis. This finding is also different to the previous understanding that circulating stem cells/precursor cells migrate into the vessel wall from the lumen and contribute to angiogenesis.…”
Section: Discussionmentioning
confidence: 50%
“…It was previously thought that compared to angiogenesis (capillary formation), arteriogenesis is a distinct process based on the remodeling and maturation of pre-existing arterioles and arteries, 1) characterized by proliferation of pre-existing smooth muscle cells (SMCs), endothelial cells (ECs), or their resident precursors. 2) Recent reports that arteriogenesis is augmented by bone marrow mononuclear cells [3][4][5] and endothelial progenitor cells suggest involvement in arteriogenesis of not only proliferation of resident cells, but also migration and proliferation of circulating stem cells/precursor cells. [6][7][8] Although previous studies have demonstrated capillary formation (vasculogenesis/angiogenesis) by transplanted cells, [7][8][9][10] they could not demonstrate incorporation of transplanted cells into pre-existing arterioles and arteries, inducing arteriogenesis.…”
mentioning
confidence: 99%
“…The increase in Nogo-B expression in tissue is likely due to increased gene expression in vascular cells as well as the recruitment of monocytes/macrophages into tissue. In this model of severe limb ischemia, it is believed that ischemia triggers the redistribution of blood flow into preformed collaterals, and the increase in shear stress concomitant with the recruitment of macrophages and macrophage-derived cytokines such as MCP-1, TNF␣, or VEGF participate in arteriogenesis in the adductor muscles, blood flow recovery, and angiogenesis in the gastrocnemius muscle (16,17,28 (29) and local macrophages may proliferate in tissue after ischemia (30), thus, the presence of residual Nogo-positive macrophages after irradiation in WT mice may contribute to the recovery of function postischemia in mice transplanted with Nogo Ϫ/Ϫ BMM. Indeed our data suggests that skeletal muscle resident macrophages exist in irradiated mice before and after ischemia, and they contribute to cytokine gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…38 The role of macrophages in the angiogenesis may occur in rapidly expanding adipose tissue, eventually leading to some degree of hypoxia. As a consequence, macrophages could contribute to the local control of fat mass expansion and of its biology.…”
Section: Role Of Infiltrating Macrophages In Watmentioning
confidence: 99%